Comparison of biodiversity and ground cover between a commercial rotationally grazed property and an adjacent nature reserve in semi‐arid rangeland. (1st November 2019) - McDonald, Sarah E.; Reid, Nick; Smith, Rhiannon; Waters, Cathleen M.; Hunter, John; Rader, Romina
Abstract: Continuous livestock grazing can have negative effects on biodiversity and landscape function in arid and semi‐arid rangelands. Alternative grazing management practices, such as rotational grazing, may be a viable option for broad‐scale biodiversity conservation and sustainable pastoral management. This study compared ground cover, plant species composition and floristic and functional diversity along gradients of grazing intensity between a pastoral property rotationally grazed by goats and an adjacent nature reserve (ungrazed by commercial livestock) in semi‐arid south‐eastern Australia. Understorey plant species composition differed significantly between the rotationally grazed property and the nature reserve, with a greater proportion and frequency of palatable species recorded in the nature reserve. Understorey plant species richness, diversity, functional biodiversity measures and ground cover declined with increasing grazing pressure close to water points under commercial rotational grazing management. However, at a whole‐paddock scale, there were few differences in plant biodiversity and ground cover between the rotationally grazed property and the nature reserve, despite differences in overall plant species composition. Flexible, adaptive, rotational grazing should be investigated further for its potential to achieve both socio‐economic and biodiversity conservation outcomes in semi‐arid rangelands to complement existing conservation reserves.